1994
DOI: 10.1002/1097-0142(19940701)74:1<142::aid-cncr2820740123>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Multiple neuropetide immunoreactivities in a renin-producing human paraganglioma

Abstract: Background. A case of a renin‐producing paraganglioma of adrenal origin with metastases to the retroperitoneal area, paravaginal area, and the ovary is reported with immunohistochemical findings indicating expression of multiple neuropeptide immunoreactivities. The patient was 23 years old at the time of diagnosis, and died from metastatic spread of the tumor 7 years later. Methods. Tumor tissue was examined by light microscopy, indirect immunohistochemistry, and electron microscopy. Results. The tumor tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…In very rare cases it occurs in extrarenal tumors such as paraganglioma and in tumors of the pancreas, lung, and ovary [3,11]. To our knowledge, this is the first documentation of paraneoplastic reninism in AML or in any hematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In very rare cases it occurs in extrarenal tumors such as paraganglioma and in tumors of the pancreas, lung, and ovary [3,11]. To our knowledge, this is the first documentation of paraneoplastic reninism in AML or in any hematological malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Human pheochromocytoma was the first tumor in which galanin was identified (Bauer et al, 1986c;Hacker et al, 1988), and later galanin-like immunoreactivity was detected in other neuroendocrine tumors, including human pituitary adenoma (Bauer et al, 1986c;Hacker et al, 1988). Subsequently, galanin-like immunoreactivity was detected in human pituitary adenoma particularly associated with adrenocorticotrophic hormone-secreting cells (Hulting et al, 1989;Vrontakis et al, 1990;Bennet et al, 1991;Hsu et al, 1991;Sano et al, 1991;Leung et al, 2002;Grenback et al, 2004) and in gangliocytoma (Sano et al, 1991;Felix et al, 1994), paraganglioma (Fried et al, 1994;Tadros et al, 2003), and neuroblastoma (Tuechler et al, 1998). Alarin was subsequently detected in differentiated neuroblastoma cells (Santic Galanin Family Peptides and Receptors et al, 2006) and was recently detected in a variety of human CNS tumors and suggested to be a diagnostic marker for ependymoma to differentiate them from other gliomas (Eberhard et al, 2013).…”
Section: Cancermentioning
confidence: 99%
“…Serum levels of neuropeptides such as atrial natriuretic protein (ANP), enkephalin, neurotensin, calcitonin and calcitonin gene related peptide (CGRP) were normal or moderately increased. Immunohistochemical analysis of the tumour also demonstrated the presence of renin and different neuropeptides (histochemical details see Fried et al ., 1994). The tumour was found to be dynorphin and enkephalin immunoreactive.…”
Section: Case Reportmentioning
confidence: 95%
“…The release of these hormones causes the clinical syndrome with attacks of palpitations, flushing, hypertension and headache. Studies of these tumours have revealed synthesis of several other categories of bioactive substances such as the peptides, neuropeptide Y (NPY), somatostatin, enkephalin, the neuroendocrine proteins (chromogranin A, synaptophysin, neurofibrillary protein (PGP 9.5)) and the structural proteins (S‐100 protein, neurone specific enolase (NSE)) (Fried et al ., 1994). Increased serum renin levels have also been reported in patients with paraganglionoma (Iwaoka et al ., 1980; Plouin et al ., 1985).…”
mentioning
confidence: 99%